Design and Simulation of Passive T-Micromixer for Improving Mixing Performance - Zainal, Qamarul Syakirin; Abd Hamid, Intan Sue Liana (Evolution in Electrical and Electronic Engineering, 2021)
In micromixer, it can be classified into two group which is passive micromixer and active micromixer. This paper would be focusing on passive micromixer which is the T-shaped micromixer which is simpler in designing when comparing to active micromixer as there are external force needed. In passive micromixer, the mixing performance depends on the geometry design of the micromixer as certain implementation can improve the mixing performance of the passive micromixer. In this analysis, two design of T micromixers were evaluated based on the T model micromixer performance. The micromixers are T-shaped micromixer with Cantor fractal structure and T-shaped micromixer with semicircular ridges. These micromixers have 5000μm channel length, 300μm channel width, inlet width and length are 300μm and 1000μm respectively. The flow rate of the inlet is set at   and the two solutions is set at the concentration of  and   to analyze the mixing performance of each of the T-shaped micromixer. T-shaped micromixer with Cantor fractal structure is analyzed to be as the better implementation on the T-shaped micromixer as it has lowest value of the standard deviation of concentration at the end of the mixing channel when compared to the other T micromixer which almost to the value of 0.